Direct and residual antimicrobial effect of 2% chlorhexidine gel, double antibiotic paste and chitosan- chlorhexidine nanoparticles as intracanal medicaments against Enterococcus faecalis and Candida albicans in primary molars: an in-vitro study - Mariem Wassel; Mohamed Radwan; Reham Elghazawy (BMC, 2023)
Abstract Background Thorough disinfection of root canals in primary molars may be complicated by the complex root canal morphology. This in-vitro study aimed to compare direct and residual antimicrobial effect of 2% chlorhexidine (CHX) gel, 500 mg/ml double antibiotic paste (DAP) and chitosan-chlorhexidine nanoparticles (CS-CHX NPs) as intracanal medicaments against Enterococcus faecalis (E. faecalis) and Candida albicans (C. albicans) in primary molars. Methods Mesial roots of 63 mandibular second primary molars were infected with E. faecalis and C. albicans. Teeth were divided into 9 groups: Ia: (CS-CHX NPs), IIa: (CHX), IIIa: (DAP), IVa: chitosan nanoparticles (CSNPs) in which medicaments were placed for 3 days, groups Ib: (CS-CHX NPs), IIb: CHX, IIIb: (DAP), IVb: (CSNPs) in which medicaments were placed for 7 days, and Group V (control): teeth were infected, irrigated with saline, and sampled 3- and 7-days post-infection. Microbiological samples were obtained after infection, 3, and 7 days after medicament placement and 7 days after medicament removal for both time points. One-way ANOVA, Tukey's post hoc test and paired t-test were used at p < 0.05. Results CS-CHX NPs had the highest anticandidal effect which was comparable to CHX and significantly higher than other medicaments (p < 0.001) at both time points. CS-CHX NPs had the highest effect against E. faecalis which was comparable to DAP and significantly higher than other medicaments (p < 0.001) at 3 days. All medicaments showed similar effect against E. faecalis after 7 days. The 7-days placement significantly increased the antimicrobial effect against both micro-organisms in all groups, except CS-CHX NPs which showed an insignificant increase. CS-CHX NPs showed the highest residual effect against both micro-organisms that increased with 7-days placement. Conclusion CSNPs and CHX combination showed a synergistic effect against both micro-organisms. CS-CHX NPs displayed a higher effect at a shorter period compared to other medicaments, yet its residual effect was higher with 7-days placement.